THE RIGHT SIDE OF ACCUMULATED DEPRECIATION. - Simon, Sidney I. (The Accounting Review, 1959)
Abstract This article says that the 1957 revision of the American Accounting Association's "Accounting and Reporting Standards for Corporate Financial Statements" adds force to the revival of an argument that has been called "the old chestnut of accounting," by omitting the statement, found in the 1948 revision, that depreciation reserves should be deducted from the related asset account in the balance sheet. The deduction of the depreciation reserve from plant account can be traced back to the early "direct write-down" method, when the consistent and systematic recording of depreciation was not understood. In years of good earnings, costs of fixed assets were written down by charges to Profit and Loss and direct credits to the fixed asset accounts. No such write-down was done in poor business years. The plant accounts thus showed arbitrary net figures which were neither cost nor value. A more convincing argument perhaps is that the depreciation reserve is not a liability and thus does not belong among the liabilities.